2014
DOI: 10.1016/j.exger.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Higher baseline serum uric acid is associated with poorer cognition but not rates of cognitive decline in women

Abstract: Serum uric acid is a powerful antioxidant that may have neuroprotective properties. While some studies have found that greater serum uric acid is associated with better cognition in older adults, it is also associated with numerous vascular risk factors that increase risk for dementia. Women may also be particularly vulnerable to the vascular effects of elevated uric acid. We previously found that mildly elevated serum uric acid is a biomarker of cognitive dysfunction in older adults, and that this likely is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 16 publications
(21 reference statements)
7
31
0
2
Order By: Relevance
“…[513] Most recently, a cohort study of 423 cognitively healthy community-dwelling older women participating in the Women’s Health and Aging Study (WHAS II) observed that a higher SUA base was associated with poorer working memory, with a trend toward slower manual speed and dexterity, after adjusting for several potential demographic and health confounders. [5] This pattern of association was replicated when a study showed that higher SUA base correlated with greater white matter atrophy [13] and cerebral ischemic burden using volume of hyperintense signal on T2-weighted brain MRI scans as a marker among older adults. [12] The latter studies indicated that the relationship between higher SUA and cognitive dysfunction may be mediated by white matter atrophy and cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[513] Most recently, a cohort study of 423 cognitively healthy community-dwelling older women participating in the Women’s Health and Aging Study (WHAS II) observed that a higher SUA base was associated with poorer working memory, with a trend toward slower manual speed and dexterity, after adjusting for several potential demographic and health confounders. [5] This pattern of association was replicated when a study showed that higher SUA base correlated with greater white matter atrophy [13] and cerebral ischemic burden using volume of hyperintense signal on T2-weighted brain MRI scans as a marker among older adults. [12] The latter studies indicated that the relationship between higher SUA and cognitive dysfunction may be mediated by white matter atrophy and cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[7, 12, 13, 19] As stated earlier, recent evidence suggests that SUA may have a beneficial or no significant cognitive effect among men, while having a potential deleterious effect among women, particularly older women. [5, 2024] The deleterious effect observed between SUA at baseline and decline in visual memory overall, may be driven by brain infarction occurring mainly among women in specific regions of the brain related to visual memory. [23] Despite the lack of effect modification by sex or by sex and age group, this association was in fact restricted to women (p<0.05 for older women, p<0.01 for younger women).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations